Observation of Orbital-Selective Dual Modulations in an Anisotropic Antiferromagnetic Kagome Metal TbTi_{3}Bi_{4} - Renjie Zhang; Bocheng Yu; Hengxin Tan; Yiwei Cheng; Feiran Shen; Junye Yang; Dan Mu; Xinru Han; Alfred Zong; Quanxin Hu; Xuezhi Chen; Yudong Hu; et al. (Physical Review X)
Orbital selectivity is pivotal in dictating the phase diagrams of multiorbital systems, with prominent examples including the orbital-selective Mott phase and superconductivity. The intercalation of anisotropic layers represents an effective method for enhancing orbital selectivity and thereby shaping the low-energy physics of multiorbital systems. Despite its potential, related experimental studies, especially those elucidating the correlation between orbital selectivity and magnetism, remain limited. In this work, we systematically examine the interplay between orbital selectivity and magnetism in the newly discovered anisotropic kagome TbTi_{3}Bi_{4} single crystal, and report the coexistence of orbital-selective dual-band modulations (q_{1}∼1/3a^{*}, q_{2}∼0.28b^{*}) within the antiferromagnetic (AFM) state. By combining soft x-ray and vacuum ultraviolet angle-resolved photoemission spectroscopy measurements, neutron powder diffraction, scanning tunneling microscopy, and density-functional-theory calculations, we identify these dual-band reconstructions as manifestations of the AFM order driven by a (approximately 1/3, 0.28, 0) nesting instability of the intercalated Tb 5d_{xz} orbitals. These orbital-selective modulations induce unusual momentum-dependent band folding and lead to the emergence of Dirac cones only at the M[over ¯]_{1} point, signaling a topological phase transition in the AFM state. Importantly, the discovery of orbital-selective (approximately 1/3, 0.28, 0) AFM order offers crucial insights into the mechanism underlying the fractional magnetization plateau in this kagome AFM metal. Our findings not only underscore the essential role of both conducting and localized electrons in determining the magnetic orders of LnTi_{3}Bi_{4} (Ln=lanthanide) kagome metals but also offer a pathway for manipulating magnetism through selective control of anisotropic electronic structures.